2007
DOI: 10.1002/ejic.200600987
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of trans‐ and cis‐[RuCl2(dmso)4] in Aqueous and Nonaqueous Solutions

Abstract: The photochemical behavior of the trans-and cis- [RuCl 2 (dmso) 4 ] complexes has been investigated in organic coordinating solvents (dmso, CH 3 CN) and aqueous solutions by means of electronic and 1 H NMR spectroscopy as well as chloride-selective electrode measurements. Excitation in the UVA and visible region of the cis-[RuCl 2 (dmso) 4 ] complex in dmso leads to geometric isomerization with quantum yields Φ 313 = 0.41 and Φ 365 = 0.49 to give the photostable trans complex, whereas in acetonitrile and aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Because CORM-2 stock solutions were prepared in DMSO, it is likely that some of the carbonyls released by CORM-2 were substituted by DMSO molecules in our experiments. Besides, it has been shown that two DMSO ligands in Ru(DMSO) 4 Cl 2 are quickly substituted by water molecules (37,38) as in iCORM-2. However, each ruthenium atom per donor is able to release only two carbonyls, retaining the third (39), making it likely that iCORM molecules contain at least one carbonyl, so we suspected that Ru(DMSO) 4 Cl 2 may not represent the main constituent of iCORM-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because CORM-2 stock solutions were prepared in DMSO, it is likely that some of the carbonyls released by CORM-2 were substituted by DMSO molecules in our experiments. Besides, it has been shown that two DMSO ligands in Ru(DMSO) 4 Cl 2 are quickly substituted by water molecules (37,38) as in iCORM-2. However, each ruthenium atom per donor is able to release only two carbonyls, retaining the third (39), making it likely that iCORM molecules contain at least one carbonyl, so we suspected that Ru(DMSO) 4 Cl 2 may not represent the main constituent of iCORM-2.…”
Section: Resultsmentioning
confidence: 99%
“…As a first approximation, we carried out docking calculations using the Patchdock server, which assigns possible docking sites according to size and geometry (46,47). As templates, we used the refined structures of the Kv1.2 channel in the open and closed conformations (48) and the compound Ru(DMSO) 2 (CO) 2 Cl 2 , which likely is a major component of CORM-2 solutions after CO release (37,38). The most common docking observed in both the open and closed states of the channel occurs at a cavity that exists between the voltage-sensing and pore domains of adjacent subunits (Fig.…”
Section: B Gray Traces)mentioning
confidence: 99%
“…The quantitative alterations might be due to change in the film thickness during the course of the drying time. Literature reports indicated that the Ru(DMSO) 4 Cl 2 exhibits reversible cis and trans linkage isomerism, in which four S-bonded DMSO's were occupied in the square planner position of the octahedral configuration for the trans form [8,9,38]. On the other hand, three out of four DMSO's are S-bonded to the Ru in a facial configuration, while the last one is O-bonded in the cis form [9,38].…”
Section: Methodsmentioning
confidence: 96%
“…Literature reports indicated that the Ru(DMSO) 4 Cl 2 exhibits reversible cis and trans linkage isomerism, in which four S-bonded DMSO's were occupied in the square planner position of the octahedral configuration for the trans form [8,9,38]. On the other hand, three out of four DMSO's are S-bonded to the Ru in a facial configuration, while the last one is O-bonded in the cis form [9,38]. In further, both the forms were reported to be involved in rapid dissolution reaction with water [38] Exact detail for the isomeric conversion within the film is unknown to us now.…”
Section: Methodsmentioning
confidence: 99%
“…(ptaMe)CF3SO3 [25] was kindly supplied by Prof. A. Romerosa (U. Almería, Spain). 1 is a light sensitive compound, [9,53] therefore its reactions were studied with the careful exclusion of light.…”
Section: General Remarksmentioning
confidence: 99%